Consumo de micronutrientes de usuários das academias da saúde de Belo Horizonte: caracterização e possível associação com o estado nutricional - Fabricia Goncalves e Bessa (2017)
Introduction: The changes in food consumption identified in recent decades, which mainly cover the increase in consumption of ultraprocessed foods to the detriment of in natura foods, are associated with negative changes in the consumption of vitamins and minerals. Such a picture appears as a risk factor for different chronic diseases, including obesity. Objective: To characterize the micronutrient consumption of users of the Health Academies of Belo Horizonte, Minas Gerais, and verify their possible association with nutritional status. Methods: Cross-sectional study with a representative sample of users of the Health Academy Program of Belo Horizonte / Minas Gerais. Anthropometric measures were used to calculate the Body Mass Index (weight / height²) and the waist-hip ratio. The investigation of food consumption was carried out from two 24-hour reminders of non-consecutive days, giving the average values of vitamins A, C and D and zinc and calcium minerals. Results: The data obtained allowed the elaboration of an original article. A total of 3193 individuals (56.28% adults and 87.97% women) were evaluated, being 63% overweight. Micronutrient inadequacy was observed regardless of nutritional status, with vitamin D being> 98% and calcium> 85%, and a higher prevalence of inadequate mineral intake among overweight individuals (88.3% vs 85.5 %). The intake of this nutrient was also lower among women with high and very high waist circumference (343.6mg vs 358.8mg, p <0.05) and was inversely related to WC (r = 0.046, p = 0.010) and WHR (r = -0.054, p = 0.002). The highest consumption (highest quartile) of vitamin A was associated with a lower chance of overweight (PR = 0.91, 95% CI = 0.84-0.98). Consumption of this nutrient was also related to WHR (r = - 0.041, p = 0.021). The higher consumption of zinc (third and fourth quartiles) was associated with a greater chance of being overweight (PR = 1.13, 95% CI 1.05 - 1.23 and RP = 1.17, 95% CI: 1, 06 - 1.28, respectively). Conclusion: Users of the Health Academy program presented a high prevalence of inadequate intake of micronutrients with an association (negative: calcium and vitamin A and positive: zinc) with nutritional status. Such nutrients may be associated with overweight, but this causality and the mechanisms involved should be better explored. The findings can subsidize strategies of food and nutritional education in the context of health promotion actions of the Health Academy.